2021
DOI: 10.21203/rs.3.rs-139016/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Public Perceptions and Attitudes of Bangladeshi Population towards Thalassemia Prevention: A Nationwide Study

Abstract: Background: Thalassemia is one of the most common life-threatening yet preventable congenital hemoglobin disorders especially in South Asian regions like Bangladesh. It has become a rising public health concern for Bangladesh as 6-12% of the population are carriers and many of them are unaware of it. The purpose of the study is to inspect the knowledge and attitude towards thalassemia among the general people of Bangladesh. Methods: A cross-sectional survey was conducted in eight administrative regions of Bang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…The research team devised a self-reported questionnaire after conducting a thorough literature review (1,2,4,7,9–14) on individuals’ thalassemia knowledge, attitudes, and practices. The questionnaire was in English.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The research team devised a self-reported questionnaire after conducting a thorough literature review (1,2,4,7,9–14) on individuals’ thalassemia knowledge, attitudes, and practices. The questionnaire was in English.…”
Section: Methodsmentioning
confidence: 99%
“…Food, sleep, living, and breathing do not affect it. Although thalassemia is a preventable disease, it's a high prevalence, and the lack of cure has made it a global health concern (2). The most prevalent clinical signs of thalassemia, classified as alpha, beta, gamma, or delta, are alpha and beta-thalassemia.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation